Understanding breast cancer patients' journey from diagnosis through survivorship. (10th August 2015) - Williams, Faustine
Abstract : Purpose: – The purpose of this paper was to understand the lived experiences of women who have been diagnosed, treated and are cancer free as survivors. Design/methodology/approach: – Using purposive sampling approach, participants were recruited from two Missouri cancer centers. A total of 15 breast cancer free women (ten white and five black) were interviewed. The participants ranged in age from 34 to 62 years, and all had at least a bachelor degree. Findings: – Eight unique themes were identified from the interviews. The women noted that maintaining positive attitude, and support from family and friends were the greatest resources that helped them through their cancer journey. They were generally positive about their experiences but uncertain what "survivor" meant individually and personally. Research limitations/implications: – All the women in this study had at least a college degree, stable family economic resources and health insurance. Originality/value: – The women interviewed in this study did not want to be called breast cancer "survivors" which is a common name for anyone who has been diagnosed, treated and cancer free. For those who are breast cancer educators, nurses, medical practitioners and counselors it is important to consider how they use the word "survivor." Referring to women who have successfully completed a treatment program for breast cancer as "survivors" attaches an identity that may not be accepted by all.